Write the sum of the series

Question:

Write the sum of the series 12 − 22 + 32 − 42 + 52 − 62 + ... + (2n − 1)2 − (2n)2.

Solution:

The given series can be rewritten as:

$3(-1)+7(-1)+11(-1)+\ldots+(4 n-1)(-1)$

$=-[3+7+11+\ldots+(4 n-1)]$

$=-\left[\frac{n}{2}\{3 \times 2+(n-1) 4\}\right]$

$=-\left[\frac{n}{2}(4 n+2)\right]$

$=-n(2 n+1)$

 

 

 

Leave a comment

Close
faculty

Click here to get exam-ready with eSaral

For making your preparation journey smoother of JEE, NEET and Class 8 to 10, grab our app now.

Download Now